Kondisi fisik siswa yang mengikuti ekstrakurikuler bola voli - Suhada, Ahmad Ikhsan; Achmad, Irfan Zinat; Gani, Ruslan Abdul (Jurnal Porkes, 2023)
The aim of this research is to determine the physical condition of students who take part in extracurricular volleyball at Pasundan Cilamaya Middle School. To answer the problem formulation that has been formulated, the author uses descriptive quantitative research, the method used in this research is parameter tests. This research was conducted at Pasundan Middle School by taking all the volleyball extracurricular athletes at Pasundan Middle School from classes VII, VIII and IX, totaling 24 people. The instrument used is a parameter test. Based on the research results, it can be seen that the physical condition of students who take part in extracurricular volleyball at Pasundan Cilamaya Middle School, the average results obtained from all students are, namely 2 people in the very low category, 4 people in the low category, 13 people in the medium category, 4 people in the high category, 1 person in the very high category. It can be concluded that the level of physical condition of students who take part in extracurricular volleyball at Pasundan Cilamaya Middle School is in the "Medium" category. Because students have just started training again and training at school and individually was stopped by the Covid pandemic, students experienced a drastic decline in their physical condition.